The Influence of Education Level on the Performance of Village Officials in Sampaga District, Mamuju Regency - Aldy; Sri Andayaningsih; Zalkha Soraya (Pustaka Digital Indonesia, 2026)
This study aims to determine the effect of education level on the performance of village officials in Sampaga District, Mamuju Regency. The population in this study was all village officials in Sampaga District, Mamuju Regency, totaling 54 people. The sampling technique used was saturated sampling, so that all members of the population were used as research samples. The research method used was a quantitative approach with data collection techniques through distributing questionnaires to respondents. Data analysis was carried out using descriptive analysis, data quality tests including validity and reliability tests, and hypothesis testing using simple linear regression analysis, t-tests, and coefficients of determination (R²). The results of the study showed that education level had a positive and significant effect on the performance of village officials. This was evidenced by a significance value of <0.05 and a calculated t-value that was greater than the t-table. The results of the regression analysis showed a unidirectional relationship between education level and village official performance, where the higher the level of education, the higher the performance of village officials tended to be. The coefficient of determination (R²) value of 0.999 indicates that 99.9% of the variation in village apparatus performance can be explained by education level, while the remaining 0.1% is influenced by other factors outside the research model. Thus, it can be concluded that education level plays a very important role in improving the performance of village apparatus in Sampaga District, Mamuju Regency.